Biosafety education practices applied to the Bettina Ferro de Souza university hospital of the Federal University of Pará (Research, Society and Development, 2023)
Hospital activities are carried out in an environment of constant exposure to occupational risk factors, therefore biosafety measures are essential for all healthcare professionals. Given the growing incidence of injuries and accidents, biosafety standards aim to prevent, minimize or eliminate risks, which can compromise the health of living beings, the environment and the quality of work. This is a qualitative and quantitative research, so the number of people available to answer the survey, based on a questionnaire with closed questions, was 32 workers. "Thus, the present research aims to determine prevention methods based on occupational risk at the Bettina Ferro de Souza University Hospital (HUBFS) which is part of the hospital complex of the Federal University of Pará (UFPA), under the coordination of the Brazilian company de Hospital Services (EBSERH). The results generated showed that most research participants are aware of and routinely use biosafety measures, but the results also showed a lack of adherence and/or perception of such measures on the part of some employees. Therefore, it is essential that all professionals are trained and qualified to correctly use biosafety equipment, to prevent accidents and occupational illnesses. It is, therefore, necessary that there are adequate working conditions, technical qualifications of all professionals, actions such as hand washing, use of PPE, equipment care, cleaning and waste management and the appropriate disposal of sharps are precautions that guarantee safety of the worker.